Unexpected Radiation-Induced Aortic Wall Thickening Requiring Composite Graft Technique during Off-Pump Coronary Artery Bypass Grafting - Paola Redaelli; Amando Gamba; Antonello Stefano Martino; Michele Triggiani (Case Reports in Surgery)
Mediastinal radiation is commonly used to treat Hodgkin’s and non-Hodgkin’s lymphoma, lung and breast cancer. Cardiac complications after radiation therapy are well described, although rare. A large spectrum of injuries can occur, causing long term morbidity among survivors. We describe a case of post-actinic ascending aortic wall thickening that prevented saphenous vein proximal anastomosis and was successfully managed with aortic no-touch off-pump coronary artery bypass grafting (OPCAB), 25 years after radiation therapy for Hodgkin’s lymphoma.